2014
DOI: 10.1186/1750-9378-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of density of schistosomal antigen expression in urinary bladder tissue on the stratification, cell type, and staging, and prognosis of carcinoma of the bladder in Egyptian patients

Abstract: BackgroundInfection with urinary schistosomiasis and its severity are oncogenic factors for developing carcinoma of the bladder, whether it is urothelial carcinoma (UC) of a transitional cell type (TCC) or non-urothelial of squamous cell carcinoma (SCC). In UC it is not defined whether it is schistosomal or not. This led to controversial results in expression of tumour markers, tumour prognosis, and response to therapy.ObjectivesWe assessed the application by immunohistochemistry method (IHC) for detection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…-The studies on the molecular basis of bladder cancer in Egypt and its changing patterns are limited [44], [45], [46], [47], [48], [49], [50].…”
Section: Limitations Of Previous Research Studies In Egyptmentioning
confidence: 99%
“…-The studies on the molecular basis of bladder cancer in Egypt and its changing patterns are limited [44], [45], [46], [47], [48], [49], [50].…”
Section: Limitations Of Previous Research Studies In Egyptmentioning
confidence: 99%
“…These metabolites are known for their carcinogenic properties. The chronic inflammation marks the onset of the disease schistosomiasis, which increases risk of urothelial hyperplasia, dysplasia, and SCC (Parkin, 2006; Wishahi et al, 2014). The infection can be acute, with symptoms like headache, fever, fatigue, abdominal pain, etc.…”
Section: Schistosoma Sppmentioning
confidence: 99%
“…22 Similar findings for the presence of parasite antigen in the body tissue have been reported in Schistosoma haematobium-associated urothelial carcinoma inflammation and cancer tissues. 23 Second, persistent biliary fibrosis may be driven by a pro-inflammatory cytokine, interleukin-6 (IL-6), released from the fibrotic tissue. 24 A previous study revealed that the level of IL-6 was eight times higher in human opisthorchiasis with advanced PDF than those without advanced PDF.…”
Section: Discussionmentioning
confidence: 99%